Nutrient Status of Saffron Growing Soils of Kishtwar District (J&K) - Vijay Kumar; Pardeep Wali, Phuntsog Tundup, A.P. Rai, A.K. Mondal (Journal of the Indian Society of Soil Science, 2016)
Twenty different saffron growing villages of Kishtwar district of Jammu and Kashmir state were selected for random soil sampling to study the available macro as well as micronutrient status of the soil. The physicochemical properties like pH, electrical conductivity (EC), organic carbon (OC), cation exchange capacity (CEC) and clay content of the soils varied from 6.65-7.47, 0.15-0.23, 5.8-8.1, 12.5-15.6 and 27.9-34.9 with mean values of 7.26, 0.19 dS m-1, 6.8 g kg-1, 13.85 [cmol(p+)kg-1] and 30.6%, respectively. None of the soils was found deficient in nitrogen (N), phosphorus (P) and potassium (K). Available N status of these soils was in medium range of 280 to 385 kg ha-1 (mean value of 331 kg ha-1), available P varied from 12.0 to 20.0 kg P2O5 ha-1 (mean value of 15.3 kg P2O5 ha-1) and 85% of the soil samples showed available K in medium range and remaining 15% samples were found with high K content. The soils were sufficient in micronutrients. Soil DTPA-extractable micro-nutrients, Zn, Cu, Mn, and Fe ranged from 1.24 to 5.55, 1.20 to 2.97, 13.2 to 47.5 and 7.17 to 17.17 mg kg-1 (mean value of 2.43, 2.09, 23.0 and 10.7 mg kg-1), respectively. Soil pH of the surface layer had a significant and negative correlation with Cu, Mn and Fe (r = -0.281**, -0.455** and -0.367**). Soil OC showed a significant positive relationship with the available N, K, Zn and Cu (r = 0.846**, 0.298*, 0.417* and 0.256*). The investigation provides preliminary information on fertility status of saffron growing soils of Kishtwar district (Jammu and Kashmir), which shall help in the formulation of nutrient management schedule in future for the better productivity of saffron.